Metode Bercerita Dalam Meningkatkan Kemampuan Berbicara Anak Usia 2-4 Tahun di KB Yasmin Kabupaten Jember - oktavia pratiwi, winda; Tukiman Hendrawijaya, Arief; Faiqotul Himmah, Irliana (JPUS: Jurnal Pendidikan Untuk Semua, 2023)
Strategies to improve children’s speaking skills that are good and appropriate need to be known and understhood by educators, so that the potentials of children’s speaking abilities can increase optimally according to the stages of their development. The purpose of this study was to describe storytelling methods in improving speaking skills aged 2-4 years at KB Yasmin, Jember Regency. The method used in this study is descriptive with a qualitative approach. Determining the research location using a purposive area. Determination of informants using purposive sampling technique. Data collection techniques using observation, interviews, and documentation. Techniques to check the validity of the data using extended observations, increased persistence and triangulation. Data analysis tenhniques use data collection, data reduction, data display and data verification. The result of the study show that will be applied so that students are interested snd enjoy listening to stories. The implementation of this storytelling method was successful in improving students’ speaking skills. Especially for the Lumajang groups of students who previously could not speak and now can speak.